Developing E-Module of Lumajang Historical Cultures for the Learning of History in the Tenth Grade with the R2D2 Model - Heriyanto, Nur Oktafiyani; Umamah, Nurul Umamah; Sumardi, Sumardi Sumardi (Lembaran Ilmu Kependidikan, 2020)
History education in the 2013 Curriculum is designed to shape the student historical awareness by engaging local history learning with national history in a series of Indonesian History. However, the lack of learning resources and knowledge of students in local history led to inadequate level of historical awareness. Based on the needs analysis of the three schools in Lumajang Regency, it shows that: (1) learning resources used by educators and students of class X are 100% textbooks and worksheets with national historical content; (2) local history-based learning resources are not widely available; and(3) 61% of students did not recognize of Lumajang's local history. Therefore that this study aims to develop e-module learning that can be used as a source of local learning history that has been validated by experts and available to increase students' historical awareness. This development research used the R2D2 (Reflective, Recursive, Design and Development) development model. The research subjects utilized 36 students of SMAN 1 Lumajang. The data collection technique of this study used observation, interviews, questionnaires and tests. The results show that the validation of material experts, linguists, and learning design experts as follows: (1) the value of 84.21% was categorizedÃ‚Â  as "good"; (2) the value of 96% was categorized as "very good"; and (3) the value of 78.33% was categorized as "good". The test result of users obtained 98% was categorized as "very good". The results of the small group trials show: (1) 87.5%; (2) 100%; (3) 87.5%; and (4) 63.5%. The results of the field trials show: (1) 100%; (2) 95%; (3) 100%; and (4) 69% which show the increase in students' historical awareness. Based on the results of these studies the e-module of local history learning can be used as a source of learning local history in schools and may improve students' historical awareness.